Possible lateral stress interactions in a sequence of large interplate thrust earthquakes on the subducting Cocos and Rivera plates - Miguel A. Santoyo (Geofísica Internacional, 2007)
Large interplate earthquakes in the Mexican subduction zone may cluster in space and time. This clustering could be due to stress interactions between large events. We investigate this possibility by calculating the coseismic Coulomb failure stress change due to seven large thrust earthquakes (Mw>7.4) that occurred from 1973 to 1985 on the Cocos plate, and from 1995 to 2003 on the Rivera plate subducting beneath the North America plate. The calculations are based on the slip distribution obtained from previous kinematic waveform inversion for these earthquakes. The calculated stress changes are superposed in a cumulative way as a function of time and space. Our results show that these earthquakes could be related to each other. At least part of the relation may possibly be attributed to the coseismic stress increase from the occurrence of previous large events in adjacent zones.